2011
DOI: 10.1108/17466661111149394
|View full text |Cite
|
Sign up to set email alerts
|

Policing youth anti‐social behaviour and crime: time for reform?

Abstract: Like many other reviews of youth justice, and proposals for reform, Time For a Fresh Start has relatively little to say about policing. Though understandable in some respects this nonetheless represents something of a missed opportunity. As gate-keepers and agenda-setters for much of the remainder of the criminal justice system, the police occupy a key position and this article consequently argues that reform programmes must focus upon the role the police play in regulating the flow of young people into the ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Following the Anti-Social Behaviour Act 2003, the police have had powers to disperse young people gathering in designated zones (HM Government, 2003, s. 30), and recent proposals suggest strengthening existing powers (Home Office, 2012). Meanwhile, it has been argued that government targets, and particularly the measurement of "offences brought to justice," have introduced perverse incentives into the policing of youthful antisocial behavior, since focusing on youth groups in schools, public space and residential homes offers an easy way to meet crime targets (Newburn, 2011). Research has suggested that young people, particularly young men, who are already known to the police are more likely to experience police contact, which can increase the likelihood of subsequent criminalization (McAra & McVie, 2010).…”
Section: The Local Governance Of Youth Crime and Antisocial Behavior mentioning
confidence: 99%
“…Following the Anti-Social Behaviour Act 2003, the police have had powers to disperse young people gathering in designated zones (HM Government, 2003, s. 30), and recent proposals suggest strengthening existing powers (Home Office, 2012). Meanwhile, it has been argued that government targets, and particularly the measurement of "offences brought to justice," have introduced perverse incentives into the policing of youthful antisocial behavior, since focusing on youth groups in schools, public space and residential homes offers an easy way to meet crime targets (Newburn, 2011). Research has suggested that young people, particularly young men, who are already known to the police are more likely to experience police contact, which can increase the likelihood of subsequent criminalization (McAra & McVie, 2010).…”
Section: The Local Governance Of Youth Crime and Antisocial Behavior mentioning
confidence: 99%
“…One risk is that PCCs will be over-responsive to high-profile local concerns which centre on 'problem youth'. Greater pressure on the police and YOTs to use their powers to criminalise young people further and decrease discretionary practice (Newburn, 2011) is a strong possibility.…”
Section: An Opportunity To Test and Evaluate The Impact Ofmentioning
confidence: 99%
“…Many described tense stigmatising encounters, in which they became caught in a double bind: experiencing both the discriminatory migrant construction and criminalizing attitudes towards BAME populations (Arnold, F o r P e e r R e v i e w 1990), particularly young men and boys (Webster, 2018). This was further accentuated by the well-documented public perceptions of the 'deviant (male) youth' (Newburn, 2011;Cohen, 2002), resulting in the creation of a 'permanent suspect population' (McAra and McVie, 2005: 27). Set within the context of a hostile political discourse and negative media representations, difficult encounters with authority led to the migrant men to question the approaches of those in power, and the amount of trust they should invest in officials who so often perceived them as problematic.…”
Section: Encountering Authority: Discrimination Risk and The Absencementioning
confidence: 99%